Comparing Presentation Summaries: Slides vs. Reading vs. Listening - Grudin, Jonathan; Gupta, Anoop; He, Li-wei; Sanocki, Elizabeth (1999)
As more audio and video technical presentations go online, it becomes imperative to give users effective summarizing and skimming tools so that they can find the presentation they want and browse through it quickly. In a previous study we reported various automated methods for summarizing audio-video of presentations, and user response. An open question remained about how well various text/image only techniques will compare to the audio-video summarizations. This study attempts to fill that gap. This paper reports a user study that compares four possible ways of allowing a user to skim a presentation: 1) PowerPoint slides used by the speaker during the presentation, 2) the text transcript created by professional transcribers from the presentation, 3) the transcript with important points highlighted by the speaker, and 4) a audio-video summary created by the speaker. Results show that although some text-only conditions can match the audio-video summary, users have a preference for audio-video. Furthermore, different styles of slide-authoring (e.g., detailed vs. big-points only) can have a big impact on their effectiveness as summaries, raising a dilemma for some speakers in authoring for on-demand previewing versus that for live audiences.